2020
DOI: 10.1371/journal.pntd.0008894
|View full text |Cite
|
Sign up to set email alerts
|

Broad diversity of Mycobacterium tuberculosis complex strains isolated from humans and cattle in Northern Algeria suggests a zoonotic transmission cycle

Abstract: Mycobacterium tuberculosis complex (MTBC) comprises closely related species responsible for human and animal tuberculosis (TB). Efficient species determination is useful for epidemiological purposes, especially for the elucidation of the zoonotic contribution. In Algeria, data on MTBC genotypes are largely unknown. In this study, we aimed to investigate the occurrence and diversity of MTBC genotypes causing human and bovine TB in Northern Algeria. During a two-year sampling period (2017–2019) in two regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 65 publications
3
17
1
Order By: Relevance
“…Those new spoligotypes received the ID numbers SB2520 (n = 1), SB2521 (n = 5), SB2522 (n = 1), and SB2523 (n = 1). Two of the four new spoligotypes, SB2520 and SB2521, have been described recently in Algerian cattle and human samples respectively [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those new spoligotypes received the ID numbers SB2520 (n = 1), SB2521 (n = 5), SB2522 (n = 1), and SB2523 (n = 1). Two of the four new spoligotypes, SB2520 and SB2521, have been described recently in Algerian cattle and human samples respectively [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…caprae in Africa. In Algeria two isolates of spoligotypes SB1451 and SB0835 were described before [ 22 , 23 ], pointing to a rare occurrence of M . caprae in this country.…”
Section: Resultsmentioning
confidence: 99%
“…In cattle the respondent in this study believed that signs were emaciation and respiratory distress with lesions seen in pulmonary organ and extra pulmonary organ. Damene et al, (2020) reported small circumscribed tubercles with yellow content in the left tracheobronchial lymph node; white-yellowish foci in the medial mediastinal lymph node; yellow necrosis in the liver; grey to white-yellowish tubercle in the uterus; gray-reddish tubercle and Large caseous mass in the lungs. Samuel et al, (2014) reported calcified and necrotic granulomas in the lungs of a bull carcass.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) a chronic bacterial disease of animals and man is characterized by progressive development of specific granulomatous lesions of tubercles in affected tissue (Shitaye et al, 2006). This disease, is wide spread in nature, infectious and a leading cause of death due to a single infectious agent (Mycobacterium) among humans in the world; Mycobacterium tuberculosis is the most common cause of human tuberculosis; however, an unknown proportion of cases are due to Mycobacterium bovis (Damene et al, 2020;Mujeeb-ur-Rahman et al, 2020). Bovine tuberculosis (bTB) is a chronic contagious zoonotic disease of both domestic and wild animals including humans, primarily caused by M. bovis (Jemal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The close relationship between the communities and cattle offers potential zoonotic transmission between cattle and humans and humans to cattle in areas where human M. tuberculosis prevalence is very high. Other people at risk of zoonotic transmission are abattoir staff who work with minimal or no understanding of the mode of transmission of zoonotic TB [64,[66][67][68]. Analysis of the spoligotypes identified one (1) M. tuberculosis (Lineage (L) 4 Cameroon sub-lineage and one (1) M. africanum (L6) in cattle samples with the M. africanum (L6) sharing spoligotype profile with human isolates SIT181/ SB0147.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%